Group size, grooming and social cohesion in primates - Lehmann, J; Korstjens, A; Dunbar, R (2007)
Most primates live in social groups in which affiliative bonds exist between individuals. Because these bonds need to be maintained through social interactions (grooming in most primates), sociality will be limited by time constraints. It has previously been shown that the time primates invest in grooming increases with group size. However, when groups become too large, individuals will not have enough time available to service all possible social relationships and group cohesion is expected to decrease. In this study, we used data from previously published studies to determine how large groups compromise on their grooming time and how ecological, phylogenetic and life history variables affect time invested in grooming (across species as well as within taxa). We used path analysis to analyse direct and indirect (via group size) effects on grooming. We showed that not only is grooming time determined by group size, but it is also affected by dispersal patterns and sex ratio. Furthermore, we found that grooming time is asymptotic when group size exceeds 40 individuals, indicating that time constraints resulting from ecological pressure force individuals to compromise on their grooming time. This was true across species, but a similar effect was also found within taxa. Cognitive constraints and predation pressure strongly affect group sizes and thereby have an indirect effect on primate grooming time. Primates that were found to live in groups larger than predicted by their neocortex size usually suffered from greater predation risk. However, most populations in our analysis were placed well within what we define as their eco-cognitive niche. © 2007 The Association for the Study of Animal Behaviour.